Biocalcification by Sporosarcina pasteurii using corn steep liquor as the nutrient source - Achal, V.; Mukherjee, Abhijit; Reddy, M. (Mary Ann Liebert Inc, 2010)
Corn steep liquor (CSL), an industrial by-product, was used as a nutrient source to grow Sporosarcina pasteurii, a bacterium used to remediate cracks and fissures in building materials and structures. Urease activity and calcite production by S. pasteurii was higher in CSL-urea medium compared to nutrient and yeast extract media. CSL can thus be used as low-cost nutrient medium for the production of urease and calcite by S. pasteurii.